A performance overview of contemporary hierarchical clustering algorithms in wireless sensor networks. (19th May 2021) - Varsa, G.V. Shaamili; Sridharan, D.
Wireless sensor networks (WSN) is a significant area in various applications and thereby becoming a research hotspot. WSN consists of a substantial number of sensor nodes powered by batteries. Energy efficiency is the most significant thing in WSN because of the non-replaceable batteries in sensor nodes. So energy upkeep is an important task in WSN. Because of the redundant deployment, WSN protocols have to scale to a large number of nodes. One of the prevalent keys to accomplish energy management and frequency reuse is clustering method. Clustering has proven to be an energy efficient method of data transmission and has many aids comprising of scalability and data aggregation. A frequency channel used in intra-cluster communication can be reused in multiple clusters. In this paper, a comparative study of the state of the art clustering algorithms in wireless sensor networks is presented. Initially, the state of the art surveys in the domain of clustering is discussed, which is then followed by the brief explanation of clustering concept, characteristics, design challenges and merits. This work provides the review of topical algorithms in the area of clustering and the classification of the same under various categories including mobility, energy efficiency, optimisation algorithms and fuzzy-based.